DNA binding properties of human Cdc45 suggest a function as molecular wedge for DNA unwinding. Issue 4 (28th November 2013) - Szambowska, Anna; Tessmer, Ingrid; Kursula, Petri; Usskilat, Christian; Prus, Piotr; Pospiech, Helmut; Grosse, Frank
Abstract: The cell division cycle protein 45 (Cdc45) represents an essential replication factor that, together with the Mcm2-7 complex and the four subunits of GINS, forms the replicative DNA helicase in eukaryotes. Recombinant human Cdc45 (hCdc45) was structurally characterized and its DNA-binding properties were determined. Synchrotron radiation circular dichroism spectroscopy, dynamic light scattering, small-angle X-ray scattering and atomic force microscopy revealed that hCdc45 exists as an alpha-helical monomer and possesses a structure similar to its bacterial homolog RecJ. hCdc45 bound long (113-mer or 80-mer) single-stranded DNA fragments with a higher affinity than shorter ones (34-mer). hCdc45 displayed a preference for 3′ protruding strands and bound tightly to single-strand/double-strand DNA junctions, such as those presented by Y-shaped DNA, bubbles and displacement loops, all of which appear transiently during the initiation of DNA replication. Collectively, our findings suggest that hCdc45 not only binds to but also slides on DNA with a 3′–5′ polarity and, thereby acts as a molecular 'wedge' to initiate DNA strand displacement.